Kepuasan Kerja: Grit dan Keseimbangan Hidup kerja dengan Motivasi Sebagai Variabel Mediasi - Aditya, Muhamad Dafa; Adiwinata, Djaka; Irawan, Irawan (Universitas Sultan Ageng Tirtayasa, 2025)
The purpose of this study is to examine the direct effect of grit and work life balance on job satisfaction, as well as their indirect effect mediated by motivation. This research employes a quantitative method with a Structural Equation Modeling (SEM) approach. The population of the study consists of 65 respondents. Data were collected through questionnaires distributed directly to employees of PT. Teras Teknik Perdana. Data analysis was conducted using SmartPLS 3.3. The result of the study showed that both grit and work life balance have a positive and significant direct on job satisfaction. Additionally, both variables also show a positive and significant indirect effect on job satisfaction through the mediating of motivation.